Implementation of an Authentic Assessment Model to Improve the Quality of Learning Assessment - Rini Agustiningsih; Dwi Rahdiyanta (Faculty of Engineering, Universitas Negeri Yogyakarta, 2019)
An assessment instrument is one of the most important factors to guarantee objectivity, fairness, and accuracy in assessing the level of students' performances in the learning process. This study aims to produce an authentic assessment model in problem solving learning. The objectives of this studyare to examine: (1) the feasibility of the developed authentic assessment model in the aspects of practicality, effectiveness, and feasibility of assessment; and (2) the accuracy of the assessment results from the authentic assessment model. This study was a research and development that adopts the Analyze, Design, Develop, Implement, and Evaluate (ADDIE) development model. The research subjects consisted of eight teachers and 44 students selected with a purposive sampling technique. This study was conducted in 4 Vocational High Schools in Yogyakarta. The research instrument validation was examined by expert judgment. The data were collected using questionnaires and observation sheets. Its data wereanalysed with descriptive statistical techniques, inter-rater reliability, inter-item correlation, and intraclass correlation.The results of the study show that (1) the developed authentic assessment model was feasible to be implemented since it fulfilled the requirements of practicality, effectiveness and implementation; and (2) the level of accuracy of the assessment results from the authentic assessment model has a very good criteria with κ mean of 0.978.